The MURKIN conspiracy - Melanson, Philip H. (New York Westport, Connecticut, 1989)
Its a significant volume that effectively demolishes the prevailing view of the assassination of Dr. King...Melanson has finally provided the public with a clear picture of the assassination...
Keywords: Science